Inflasi Dalam Pertumbuhan Ekonomi: Studi Empiris di Indonesia Periode 1991 – 2024 - Mukarramah, Mukarramah; Zulkarnain, M.; Arif, Ramadhana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
This study seeksto examine impact of inflation on economic growth within a macroeconomic framework. The analysis utilizes time series gauging spanning from 1991 to 2024. A simpe linear regression model wa employed, along with the coefficient of determination and t-statistical test, facilitated through the use of Eviews 12 Software. The findings reveal that inflation exert a atatistically significant negative effect on national economic growth. The coefficient of determination indicates that 70,76 percen of the variation in economic growth is a accounted fot by the inflation variabel. Furthermore, the result of the t-test confirm that inflation significantly influences economic growth in the Indonesia context.